Code Mixing in WhatsApp Chats Made by Bilingual Immigrant of Pakistan - Andi Adisaturrahimi; Muhammad Zaki Pahrul Hadi (Humanitatis : Journal of Language and Literature, 2023)
This study aimed to analyze the types of code mixing, especially those found on WhatsApp social media made by bilingual immigrants of Pakistan in everyday life. The descriptive methodology was utilized by the researchers to carry out this study, which concentrated on code-mixing. This study examined how English was used by immigrants to connect with friends in Malaysia, Indonesia, and other countries as well as with friends who were also immigrants from Pakistan who were living in Makassar. The research subject has been living in Makassar for three years. Data was obtained through observation on the WhatsApp of the Bilingual Immigrant account. In order to assess the data, Hoffman's (1991) theory was used. Data analysis revealed that there were five instances of "Intra-Sentential" code-mixing, five instances of "Intra-lexical" code-mixing, and zero instances of code-mixing "involving a change of pronunciation".